Optimization of the performance of M-Cycle indirect evaporative cooling via thermodynamic approach - Chenxia Jia; Daxi Sun; Xingfu Hu; Chengjun Jing (Journal of Asian Architecture and Building Engineering, 2023)
For the further energy conservation, the study on the optimizing the M-Cycle indirect evaporative cooling (MIEC) performance is meaningful. With the aim of the optimization, a model of a general MIEC system was established, the thermodynamic entropy production optimization method was used to fully reflect the energy quality and irreversibility. The inlet parameters, supply air ratio, dew point temperature efficiency, unit-cooling capacity and Entropy Production Number were used to analyze and improve the cooling and thermodynamic performance of the general MIEC. A total of 6750 air treatment processes have been studied with the self-programmed FORTRA. It is concluded that when the inlet temperature is high, with the increase in inlet relative humidity, the unit-cooling capacity of the system greatly improves while the Entropy Production Number increases relatively small. When the ambient humidity variation range is large, the irreversible loss of the system can be reduced by coordinating the supply air ratio and dew point temperature efficiency of the MIEC system. Ultimately, the results of this study will provide theoretical reference for the design and operation of the practical engineering of the MIEC.